Encapsulating material composition for optical elements and encapsulating material film for optical elements using the same

The encapsulating material composition for optical elements, featuring an olefin copolymer and a compound from a specific chemical formula as a crosslinking aid, addresses the challenges of high volume resistance and productivity in solar cell encapsulation materials by ensuring rapid impregnation and excellent light transmittance.

JP7648295B2Active Publication Date: 2025-03-18LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023566696
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-10
Filing Date
2022-11-10
Publication Date
2025-03-18
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

Existing solar cell encapsulation materials face challenges with high volume resistance and productivity, particularly when using ethylene/alpha-olefin copolymers, which suffer from reduced mixability with polar crosslinking aids and prolonged impregnation times.

Method used

The development of an encapsulating material composition for optical elements that includes an olefin copolymer, a crosslinking agent, a silane coupling agent, and a compound represented by a specific chemical formula, which acts as a crosslinking aid to improve mixability and impregnation speed.

Benefits of technology

The proposed solution achieves high volume resistance, rapid impregnation, excellent light transmittance, and improved adhesion, thereby enhancing the productivity and performance of solar cell encapsulation materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648295000010
    Figure 0007648295000010
  • Figure 0007648295000011
    Figure 0007648295000011
  • Figure 0007648295000012
    Figure 0007648295000012
Patent Text Reader

Abstract

The present invention relates to an encapsulant composition for optical elements containing an ethylene / alpha-olefin copolymer having high volume resistivity and light transmittance, and an encapsulant film for optical elements using the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0154112 filed on November 10, 2021, and all contents disclosed in the documents of said Korean patent application are incorporated by reference into this specification.

[0002] The present invention relates to an encapsulant composition for optical elements having high volume resistance and light transmittance, and an encapsulant film for optical elements using the same. [Background technology]

[0003] As global environmental problems and energy problems become increasingly serious, solar cells are attracting attention as a means of generating clean energy that will not run out. When solar cells are used outdoors, such as on the roofs of buildings, they are generally used in the form of modules. When manufacturing a solar cell module, in order to obtain a crystalline solar cell module, a protective sheet for the solar cell module (front side transparent protective member) / solar cell encapsulant / crystalline solar cell element / solar cell encapsulant / protective sheet for the solar cell module (rear side protective member) are laminated in this order. On the other hand, in order to obtain a thin-film solar cell module, a thin-film solar cell element / solar cell encapsulant / protective sheet for the solar cell module (rear side protective member) are laminated in this order.

[0004] As the above-mentioned solar cell encapsulant, generally, ethylene / vinyl acetate copolymer, ethylene / alpha-olefin copolymer, etc. are used. In addition, the solar cell encapsulant usually contains a light stabilizer as an additive because it is required to have long-term weather resistance. In addition, in consideration of the adhesion of the front transparent protective member or the back protective member, which is typified by glass, the solar cell encapsulant usually contains a silane coupling agent.

[0005] Specifically, ethylene / vinyl acetate copolymer (EVA) sheets have been widely used due to their excellent transparency, flexibility, and adhesive properties. Ethylene-vinyl acetate copolymer (EVA) films are widely used due to their excellent transparency, flexibility, and adhesive properties. However, when EVA compositions are used as a constituent material of solar cell encapsulants, there is concern that components such as acetic acid gas generated by the decomposition of EVA may affect solar cell elements.

[0006] Ethylene / alpha-olefin copolymers do not have the problem of resin hydrolysis, and therefore they have been able to solve the problems of reduced lifespan and reduced reliability. However, because the resin of ethylene / alpha-olefin copolymers does not contain polar groups, they have poor mixability with polar crosslinking assistants contained in the constituent materials of existing solar cell encapsulants, and impregnation takes a very long time, which has led to productivity problems.

[0007] As described above, there is a need to develop a crosslinking assistant capable of improving the productivity of solar cell encapsulant containing ethylene / alpha-olefin copolymer, which has excellent volume resistivity and can be effectively used as a material that requires high insulation properties, such as solar cell encapsulant. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 2018-0063669 Summary of the Invention [Problem to be solved by the invention]

[0009] The problem to be solved by the present invention is to provide an encapsulant composition for optical elements that contains a crosslinking aid that has excellent miscibility with an olefin-based copolymer and exhibits high volume resistivity and therefore excellent insulating properties.

[0010] Another object of the present invention is to provide an encapsulant film for optical elements produced by using the encapsulant composition for optical elements.

[0011] It is still another object of the present invention to provide an optical element module including the optical element encapsulant film. [Means for solving the problem]

[0012] In order to solve the above problems, the present invention provides an encapsulant composition for optical elements, an encapsulant film for optical elements, and an optical element module.

[0013] [1] The present invention provides an encapsulant composition for optical elements, comprising (1) an olefin copolymer, (2) a crosslinking agent, (3) a silane coupling agent, and (4) a compound represented by the following chemical formula 1: [ka] In the above Chemical Formula 1, l, m, n, and o each independently represent an integer of 0 to 4.

[0014] [2] The present invention provides an encapsulant composition for optical elements in the above-mentioned [1], wherein the olefin-based copolymer (1) satisfies the following requirements: (a) density 0.85-0.90 g / cc, and (b) melt index 0.1-100 g / 10 min.

[0015] [3] The present invention provides the encapsulant composition for optical elements according to the above [1] or [2], wherein the (1) olefin copolymer is an ethylene alpha-olefin copolymer.

[0016] [4] The present invention relates to any one of the above items [1] to [3], wherein the olefin copolymer (1) has a volume resistivity of 1.0×10 15 The present invention provides an encapsulant composition for optical elements, which is an ethylene alpha-olefin copolymer having a resistivity of Ω·cm or more.

[0017] [5] The present invention provides an encapsulant composition for optical elements in any one of the above items [1] to [4], wherein the crosslinking agent is one or more selected from the group consisting of organic peroxides, hydroperoxides and azo compounds.

[0018] [6] The present invention relates to any one of the above [1] to [5], wherein the crosslinking agent is t-butylcumyl peroxide, di-t-butyl peroxide, di-cumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, t-butyl hydroperoxide, bis-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, t-butylperoxyisobutylene The present invention provides an encapsulant composition for optical elements, which is at least one selected from the group consisting of tert-butyl peroxyacetate, tert-butyl peroxy-2-ethylhexyl carbonate (TBEC), tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxyoctoate, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxybenzoate, di-tert-butyl peroxyphthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne, methyl ethyl ketone peroxide, cyclohexanone peroxide, azobisisobutyronitrile, and azobis(2,4-dimethylvaleronitrile).

[0019] [7] The present invention provides an encapsulant composition for optical elements in any one of the above [1] to [6], wherein the silane coupling agent is one or more selected from the group consisting of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane (MEMO), vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and p-styryltrimethoxysilane.

[0020] [8] The present invention provides an encapsulant composition for optical elements in any one of the above [1] to [7], wherein in Chemical Formula 1, l, m, n, and o each independently represent an integer of 0 to 2.

[0021] [9] The present invention provides the encapsulant composition for optical elements in any one of the above [1] to [8], wherein the compound of Chemical Formula 1 is tetravinyltin.

[0022]

[10] The present invention provides an encapsulant composition for optical elements in any one of the above [1] to [9], comprising: (1) 80 to 99 parts by weight of an olefin copolymer; (2) 0.1 to 9 parts by weight of an organic peroxide; (3) 0.01 to 2 parts by weight of a silane coupling agent; and (4) 0.1 to 9 parts by weight of a compound represented by Chemical Formula 1.

[0023]

[11] The present invention provides an encapsulant composition for optical elements in any one of the above items [1] to

[10] , further comprising (5) a cross-linking auxiliary other than the compound of Chemical Formula 1, the (5) cross-linking auxiliary including a compound having one or more allyl groups or (meth)acryloxy groups.

[0024]

[12] The present invention provides an encapsulant composition for optical elements in the above

[11] , wherein the (5) crosslinking auxiliary comprises one or more selected from the group consisting of triallyl isocyanurate (TAIC), triallyl cyanurate, diallyl phthalate, diallyl fumarate, diallyl maleate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, and trimethylolpropane trimethacrylate.

[0025]

[13] The present invention provides the encapsulant composition for optical elements according to the above

[11] or

[12] , wherein a weight ratio of the compound of (4) chemical formula 1 and the crosslinking auxiliary (5) is 20:80 to 80:20.

[0026]

[14] The present invention provides an encapsulant film for optical elements, comprising an olefin copolymer and a compound represented by the following Chemical Formula 1: [ka] In the above Chemical Formula 1, l, m, n, and o each independently represent an integer of 0 to 4.

[0027]

[15] The present invention provides an optical element module including an optical element and the encapsulant film for optical elements according to

[14] above. Effect of the Invention

[0028] The encapsulant composition for optical elements of the present invention contains a tin-containing compound, which has excellent miscibility with an olefin-based copolymer, as a crosslinking assistant, and thus exhibits excellent volume resistivity and light transmittance, and can therefore be widely used in various applications in the electric and electronic industry. [Brief description of the drawings]

[0029] [Figure 1] 1 is a graph showing impregnation torque curves plotted against the stirring time when the ethylene / 1-butene copolymers measured in Examples 1 to 5 are impregnated with a crosslinking agent, a crosslinking coagent, and a silane coupling agent. [Diagram 2] 1 is a graph showing impregnation torque curves plotted against a stirring time when a crosslinking agent, a crosslinking coagent, and a silane coupling agent are impregnated into an ethylene / 1-butene copolymer measured in Comparative Example 1. [Diagram 3] 1 is a graph showing impregnation torque curves plotting impregnation torque values ​​as a function of stirring time when a crosslinking agent, a crosslinking coagent, and a silane coupling agent are impregnated into an ethylene / 1-butene copolymer measured in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The present invention will now be described in further detail in order to facilitate understanding of the present invention.

[0031] The terms and words used in the description of the present invention and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of the terms in order to best describe their invention.

[0032] [Sealant composition for optical elements] The encapsulant composition for optical elements of the present invention is characterized by comprising (1) an olefin copolymer, (2) a crosslinking agent, (3) a silane coupling agent, and (4) a compound represented by the following chemical formula 1:

[0033] [ka]

[0034] In the above Chemical Formula 1, l, m, n, and o each independently represent an integer of 0 to 4.

[0035] The present invention relates to an encapsulant composition for optical elements having high volume resistivity and excellent electrical insulation. Specifically, the encapsulant composition for optical elements of the present invention contains an olefin-based copolymer instead of ethylene vinyl alcohol (EVA) that has been used in conventional encapsulant compositions for optical elements, thereby solving the problem of the acetate group of ethylene vinyl alcohol being hydrolyzed to form acetic acid in a humid environment, and improving the durability and reliability of the optical element module. In addition, by applying the compound represented by the above chemical formula 1 as a crosslinking assistant to the olefin-based copolymer, the problem of the polar crosslinking assistant used in the existing ethylene vinyl alcohol (EVA) not being sufficiently miscible with the olefin-based copolymer not containing a polar group, and thus delaying the impregnation of the crosslinking agent, can be solved, and a high degree of crosslinking, volume resistivity, and light transmittance can be achieved.

[0036] (1) Olefin copolymer The (1) olefin copolymer contained in the encapsulant composition for optical elements according to one example of the present invention can satisfy (a) a density of 0.85 to 0.90 g / cc and (b) a melt index of 0.1 to 100 g / 10 min.

[0037] The density (a) of the olefin copolymer may be specifically 0.850 g / cc or more, 0.855 g / cc or more, 0.860 g / cc or more, 0.865 g / cc or more, 0.870 g / cc to 0.900 g / cc or less, 0.895 g / cc or less, 0.890 g / cc or less, 0.885 g / cc or less, 0.880 g / cc or less, 0.875 g / cc or less, or 0.870 g / cc or less. If the density of the olefin copolymer is too high, the light transmittance of the encapsulant composition for optical elements and the encapsulant for optical elements produced therefrom may decrease due to the crystal phase contained in the olefin copolymer, but if the olefin copolymer satisfies the density range, it may exhibit high light transmittance.

[0038] The (b) melt index of the olefin copolymer may be 0.1 g / 10 min or more, 0.5 g / 10 min or more, 1.0 g / 10 min or more, 1.5 g / 10 min or more, 2.0 g / 10 min or more, 2.5 g / 10 min or more, 5.0 g / 10 min or more, or 10.0 g / 10 min or more to 100 g / 10 min or less, 95 g / 10 min or less, 90 g / 10 min or less, 85 g / 10 min or less, 80 g / 10 min or less, 75 g / 10 min or less, 70 g / 10 min or less, 60 g / 10 min or less, or 50 g / 10 min or less. If the melt index of the olefin-based copolymer is too low or too high outside the above range, the moldability of the encapsulant composition for optical elements may be poor, making it difficult to stably extrude the composition. However, if the olefin-based copolymer satisfies the above range of melt index, the encapsulant composition for optical elements has excellent moldability, and an encapsulant for optical elements and an encapsulant sheet for optical elements can be stably extruded.

[0039] The (1) olefin copolymer contained in the encapsulant composition for optical elements according to one embodiment of the present invention may be an ethylene / alpha-olefin copolymer.

[0040] Generally, the density of an ethylene / alpha-olefin copolymer is affected by the type and content of the monomer used during polymerization, the degree of polymerization, etc., and in the case of a copolymer, it is greatly affected by the content of the comonomer. Here, the higher the comonomer content, the lower the density of the ethylene / alpha-olefin copolymer can be produced, and the content of the comonomer that can be introduced into the copolymer may depend on the specific copolymerization of the catalyst.

[0041] The ethylene / alpha-olefin copolymer contained in the encapsulant composition for optical elements of the present invention exhibits the above-mentioned low density and can exhibit excellent processability.

[0042] The ethylene / alpha-olefin copolymer is prepared by copolymerizing ethylene with an alpha-olefin monomer. The alpha-olefin, which means a portion of the copolymer derived from the alpha-olefin monomer, is an alpha-olefin having C4 to C20, specifically, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, or 1-eicosene, and may be one of these alone or a mixture of two or more of them.

[0043] Among them, the alpha-olefin can be 1-butene, 1-hexene or 1-octene, preferably 1-butene, 1-hexene or a combination thereof.

[0044] In addition, the content of the alpha-olefin in the ethylene / alpha-olefin copolymer may be appropriately selected within a range that satisfies the above physical property requirements, and specifically, may be more than 0 and up to 99 mol%, or 10 to 50 mol%, but is not limited thereto.

[0045] In one example of the encapsulant composition for optical elements of the present invention, the (1) olefin copolymer has a volume resistivity of 1.0×10 15 The ethylene alpha-olefin copolymer may have a modulus of 3.0×10 15 Ω cm or more, 5.0×10 15 Ω cm or more, 7.0×10 15 Ω cm or more, 1.0×10 16 Ω cm or more, 3.0×10 16 Ω cm or more, or 5.0×10 16The volume resistivity of the olefin copolymer (1) can be a copolymer having a volume resistivity of Ω·cm or more. If the volume resistivity of the olefin copolymer (1) is too low, the volume resistivity of the encapsulant composition for optical elements after crosslinking cannot reach an appropriate level, but if the volume resistivity of the olefin copolymer (1) satisfies the above value, the encapsulant composition for optical elements can exhibit excellent volume resistivity after crosslinking. The upper limit of the volume resistivity of the olefin copolymer (1) is not particularly limited, but taking into consideration the volume resistivity that an olefin copolymer normally exhibits and the inconvenience of producing an olefin copolymer with a high volume resistivity, it is preferable that the upper limit be 9.9×10 16 Ω cm or less, 9.0×10 16 Ω cm or less, 7.0×10 16 Ω cm or less, 5.0×10 16 Ω cm or less, 3.0×10 16 Ω cm or less, 2.5×10 16 Ω cm or less, or 2.0×10 16 A value of Ω·cm or less can be used.

[0046] (2) Crosslinking agent The crosslinking agent may be any crosslinking compound known in the art that can initiate radical polymerization or form a crosslinking bond, and may be one or more crosslinking agents selected from the group consisting of organic peroxides, hydroperoxides, and azo compounds.

[0047] In one embodiment of the present invention, the crosslinking agent may specifically be an organic peroxide.

[0048] The organic peroxide may be an organic peroxide having a one-hour half-life temperature of 120 to 135°C, for example, 120 to 130°C, 120 to 125°C, preferably 121°C. The "one-hour half-life temperature" refers to a temperature at which the half-life of the crosslinking agent is one hour. The temperature at which a radical initiation reaction is efficiently carried out varies depending on the one-hour half-life temperature. Therefore, when an organic peroxide having a one-hour half-life temperature in the above range is used as a crosslinking agent, a radical initiation reaction, i.e., a crosslinking reaction, can be effectively carried out at a lamination process temperature for manufacturing an optoelectronic device.

[0049] Examples of the crosslinking agent include dialkyl peroxides such as t-butylcumyl peroxide, di-t-butyl peroxide, di-cumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexane; hydroperoxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, and t-butyl hydroperoxide; diacyl peroxides such as bis-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide, and 2,4-dichlorobenzoyl peroxide; t-butylperoxyisobutyrate, t-butylperoxyacetate, Examples of the peroxyesters include t-butylperoxy-2-ethylhexyl carbonate (TBEC), t-butylperoxy-2-ethylhexanoate, t-butylperoxypivalate, t-butylperoxyoctoate, t-butylperoxyisopropyl carbonate, t-butylperoxybenzoate, di-t-butylperoxyphthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne; and ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide, and azo compounds such as lauryl peroxide, azobisisobutyronitrile, and azobis(2,4-dimethylvaleronitrile), but the present invention is not limited thereto.

[0050] (3) Silane coupling agents The silane coupling agent can be, for example, one or more selected from the group consisting of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane (MEMO), vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and p-styryltrimethoxysilane.

[0051] (4) Compound of formula 1 The encapsulant composition for optical elements of the present invention contains a compound represented by the following Chemical Formula 1.

[0052] [ka]

[0053] In the above Chemical Formula 1, l, m, n, and o each independently represent an integer of 0 to 4.

[0054] In addition, in the above chemical formula 1, l, m, n, and o can each independently be an integer of 0 to 2.

[0055] In addition, the encapsulant composition for optical elements according to an embodiment of the present invention may specifically include tetravinyltin as the compound of the following Chemical Formula 1.

[0056] The compound of Chemical Formula 1 may be included in an encapsulant composition for optical elements as a crosslinking aid, and since the compound of Chemical Formula 1 has a relatively low polarity compared to compounds containing an allyl group such as triallyl isocyanurate (TAIC) that have been used as existing crosslinking aids, it can exhibit excellent miscibility with the (1) olefin copolymer contained in the encapsulant composition for optical elements of the present invention, thereby shortening the impregnation time of the crosslinking aid. In addition, when an encapsulant for optical elements is manufactured using the encapsulant composition for optical elements containing the compound of Chemical Formula 1 as a crosslinking aid, the manufactured encapsulant for optical elements can exhibit high volume resistance.

[0057] An encapsulant composition for optical elements according to one embodiment of the present invention may include (1) 80 to 99 parts by weight of the olefin copolymer, (2) 0.1 to 9 parts by weight of the crosslinking agent, (3) 0.01 to 2 parts by weight of the silane coupling agent, and (4) 0.1 to 9 parts by weight of the compound of Chemical Formula 1. The content of each component may refer to the relative ratio between the weights of each component included in the encapsulant composition for optical elements.

[0058] The (1) olefin-based copolymer may be included in an amount of 80 to 99 parts by weight, specifically, 80 parts by weight or more, 82 parts by weight or more, 85 parts by weight or more, 86 parts by weight or more, 87 parts by weight or more, 88 parts by weight to 99 parts by weight or less, 98 parts by weight or less, 97 parts by weight or less, 96 parts by weight or less, or 95 parts by weight or less. If the content of the (1) olefin-based copolymer is too small, the mechanical properties such as tear resistance and tear strength of the optical element encapsulant are not adequately exhibited, so when the (1) olefin-based copolymer is included in the entire optical element encapsulant composition in the above range, the optical element encapsulant can exhibit appropriate mechanical properties.

[0059] The (2) crosslinking agent may be included in an amount of 0.1 to 9 parts by weight, specifically, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.4 parts by weight or more, 0.5 parts by weight or more, 0.6 parts by weight or more, 0.7 parts by weight or more, 0.8 parts by weight or more, or 1 part by weight or more to 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, or 3 parts by weight or less. If the content of the (2) crosslinking agent is too small, the crosslinking reaction is difficult to proceed, and if the content of the (2) crosslinking agent is too large, the volume resistance of the optical element encapsulant decreases. Therefore, when the (2) crosslinking agent is included in the entire optical element encapsulant composition in the above range, the optical element encapsulant composition can be appropriately crosslinked to be manufactured as an optical element encapsulant, and the manufactured optical element encapsulant can exhibit high volume resistance.

[0060] The (3) silane coupling agent may be included in an amount of 0.01 to 2 parts by weight, specifically, 0.01 parts by weight or more, 0.02 parts by weight or more, 0.05 parts by weight or more, 0.07 parts by weight or more, 0.09 parts by weight or more, 0.1 parts by weight or more, or 0.15 parts by weight or more to 2 parts by weight or less, 1.8 parts by weight or less, 1.7 parts by weight or less, 1.5 parts by weight or less, 1.2 parts by weight or less, 1.0 parts by weight or less, 0.8 parts by weight or less, 0.7 parts by weight or less, 0.5 parts by weight or less, or 0.4 parts by weight or less. If the content of the (3) silane coupling agent is too small, the adhesive strength of the encapsulant composition for optical elements to the substrate, for example, the adhesive strength of the encapsulant composition for optical elements to the glass substrate, is low, making it difficult to exhibit appropriate performance as an encapsulant for optical elements, and if the content of the (3) silane coupling agent is too large, the volume resistance of the encapsulant for optical elements is reduced, which is not appropriate. When the (3) silane coupling agent is contained in the entire encapsulant composition for optical elements within the above range, the encapsulant composition for optical elements exhibits excellent adhesion to the substrate of the optical element or the glass substrate on which the optical element is located, and effectively prevents moisture penetration, etc., allowing the optical element to maintain excellent performance for a long period of time, and the encapsulant for optical elements can exhibit high volume resistance.

[0061] The compound of formula (4) may be included in an amount of 0.1 to 9 parts by weight, specifically, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.4 parts by weight or more, 0.5 parts by weight or more, 0.6 parts by weight or more, 0.7 parts by weight or more, 0.8 parts by weight or more, or 1 part by weight or more to 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, or 3 parts by weight or less. If the content of the compound of formula (4) 1 is too small, the crosslinking reaction is difficult to occur, and if the content of the compound of formula (4) 1 is too large, the volume resistance of the encapsulant for optical elements is reduced. Therefore, when the compound of formula (4) 1 is included in the entire encapsulant composition for optical elements in the above range, the encapsulant composition for optical elements can be appropriately crosslinked to be manufactured into an encapsulant for optical elements, and the manufactured encapsulant for optical elements can exhibit high volume resistance.

[0062] The encapsulant composition for optical elements may further contain (5) a crosslinking assistant other than the compound of Chemical Formula 1.

[0063] As the (5) crosslinking aid, various crosslinking aids known in the art may be used, and may include, for example, a compound having at least one unsaturated group such as an allyl group or a (meth)acryloxy group.

[0064] Examples of the (5) crosslinking aid include polyallyl compounds such as triallyl isocyanurate (TAIC), triallyl cyanurate, diallyl phthalate, diallyl fumarate, and diallyl maleate, and examples of the compound containing a (meth)acryloxy group include poly(meth)acryloxy compounds such as ethylene glycol diacrylate, ethylene glycol dimethacrylate, and trimethylolpropane trimethacrylate, but are not limited thereto.

[0065] When the encapsulant composition for optical elements according to one embodiment of the present invention further includes a cross-linking auxiliary (5) other than the compound of Chemical Formula 1, the weight ratio of the compound of Chemical Formula 1 (4) and the cross-linking auxiliary (5) may be 20:80 to 80:20, specifically, 21:79 to 79:21, 22:78 to 78:22, 23:77 to 77:23, 24:76 to 76:24, or 25:75 to 75:25. When the encapsulant composition for optical elements according to one embodiment of the present invention further includes a cross-linking auxiliary (5) other than the compound of Chemical Formula 1, the total amount of the compound of Chemical Formula 1 (4) and the cross-linking auxiliary (5) may be included in an amount of 0.1 to 9 parts by weight, specifically, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.4 parts by weight or more, 0.5 parts by weight or more, 0.6 parts by weight or more, 0.7 parts by weight or more, 0.8 parts by weight or more, or 1 part by weight to 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, or 3 parts by weight or less.

[0066] When the encapsulant composition for optical elements according to one embodiment of the present invention contains both the compound of formula (4) and the crosslinking aid (5), it can satisfy high volume resistance, rapid immersion speed, excellent light transmittance and adhesion, and can achieve a higher degree of crosslinking than when only the compound of formula (4) is used. When both the compound of formula (4) and the crosslinking aid (5) are contained, and the light transmittance for the same amount of crosslinking aid is increased as the ratio of the crosslinking aid (5) to the compound of formula (4) increases, and the immersion speed, volume resistance and degree of crosslinking are improved as the ratio of the crosslinking aid (5) decreases, the ratio can be appropriately determined within the above range according to the physical properties to be exhibited.

[0067] Furthermore, the encapsulant composition for optical elements may further contain, as necessary, one or more additives selected from a light stabilizer, a UV absorber, a heat stabilizer, and the like.

[0068] The light stabilizer can capture active species that initiate photodegradation of the resin and prevent photooxidation depending on the application of the composition. The type of light stabilizer that can be used is not particularly limited, and known compounds such as hindered amine compounds or hindered piperidine compounds can be used.

[0069] The UV absorbent can absorb ultraviolet rays from sunlight or the like depending on the application of the composition, convert them into harmless heat energy in the molecule, and prevent the excitation of active species that initiate photodegradation in the resin composition. The specific type of UV absorbent that can be used is not particularly limited, and for example, one or a mixture of two or more inorganic UV absorbents such as benzophenone-based, benzotriazole-based, acrylonitrile-based, metal complex salt-based, hindered amine-based, ultrafine titanium oxide or ultrafine zinc oxide can be used.

[0070] Examples of the heat stabilizer include phosphorus-based heat stabilizers such as tris(2,4-di-tert-butylphenyl)phosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl ester phosphorous acid, tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphonate, and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite; and lactone-based heat stabilizers such as a reaction product of 8-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene. One or more of the above may be used.

[0071] The content of the light stabilizer, UV absorber and / or heat stabilizer is not particularly limited. That is, the content of the additives can be appropriately selected in consideration of the use of the resin composition, the shape and density of the additives, etc., and can be appropriately adjusted within the range of 0.01 to 5 parts by weight based on 100 parts by weight of the total solid content of the encapsulant composition for optical elements.

[0072] In addition to the above components, the encapsulant composition for optical elements of the present invention can further contain various additives known in the art depending on the application of the resin component.

[0073] In addition, the encapsulant composition for optical elements can be molded by injection, extrusion, or other methods to be used as various molded products. Specifically, it can be used as an encapsulant for encapsulating elements in various optoelectronic devices, such as solar cells, and can also be used as an industrial material applied to, for example, a temperature-raising lamination process, but is not limited thereto.

[0074] [Optical element encapsulant film and optical element module] The present invention also provides an encapsulant film for optical devices, comprising an olefin copolymer and a compound represented by the following Chemical Formula 1:

[0075] [ka]

[0076] In the above Chemical Formula 1, l, m, n, and o each independently represent an integer of 0 to 4.

[0077] In addition, in the above chemical formula 1, l, m, n, and o can each independently be an integer of 0 to 2.

[0078] In addition, the encapsulant composition for optical elements according to an embodiment of the present invention may specifically include tetravinyltin as the compound of the following Chemical Formula 1.

[0079] The olefin copolymer and the compound of Chemical Formula 1 are as described above.

[0080] The present invention also provides an encapsulant film for optical elements, comprising the encapsulant composition for optical elements.

[0081] The encapsulant film for optical elements of the present invention can be produced by forming a composition containing the olefin copolymer and a compound represented by the following Chemical Formula 1 into a film or sheet shape, and specifically, can be produced by forming the encapsulant composition for optical elements into a film or sheet shape. The forming method is not particularly limited, and can be produced by, for example, forming a sheet or film through a common process such as a T-die process or extrusion. For example, the encapsulant film for optical elements can be produced in an in situ process using an apparatus in which a process for producing a resin composition using the encapsulant composition for optical elements and a process for forming a film or sheet are connected to each other.

[0082] The thickness of the encapsulant film for optical elements may be adjusted to about 10 to 2,000 μm or about 100 to 1,250 μm in consideration of the supporting efficiency and breakage possibility of elements in an optoelectronic device, weight reduction and workability of the device, and may be changed according to specific applications.

[0083] The present invention also provides an optical element module including an optical element and the optical element encapsulant film. The optical element may be, for example, a solar cell, and the optical element module may be a solar cell module. In the present invention, the optical element module may have a configuration in which the optical element cells, for example, solar cell cells, arranged in series or parallel are filled with the optical element encapsulant film of the present invention, a glass surface is arranged on the surface exposed to sunlight, and the back surface is protected by a back sheet, but is not limited thereto, and various types and forms of optical element modules or solar cell modules manufactured using the optical element encapsulant film in the art may be applied to the present invention.

[0084] The glass surface may be made of tempered glass in order to protect the optical element from external impact and prevent damage, and may be made of low iron tempered glass in order to prevent solar light reflection and increase solar light transmittance, but is not limited thereto.

[0085] The back sheet is a weather-resistant film that protects the back surface of the optical element module from the outside, and examples thereof include, but are not limited to, a fluorine-based resin sheet, a metal plate or foil such as aluminum, a cyclic olefin-based resin sheet, a polycarbonate-based resin sheet, a poly(meth)acrylic resin sheet, a polyamide-based resin sheet, a polyester-based resin sheet, and a composite sheet obtained by laminating a weather-resistant film and a barrier film.

[0086] In addition, the optical element module of the present invention can be produced without limitation according to methods well known in the art, except that it contains the above-mentioned encapsulant film for optical elements.

[0087] The optical element module of the present invention is manufactured using an optical element encapsulant film having excellent volume resistivity, and can prevent electrons in the optical element module from moving through the optical element encapsulant film and causing current to flow out to the outside. Therefore, it is possible to significantly suppress the PID (Potential Induced Degradation) phenomenon, in which insulation deteriorates, causing leakage current and resulting in a sudden drop in module output.

[0088] Working Example The present invention will be described in more detail with reference to the following examples. However, the following examples are merely for the purpose of illustrating the present invention and are not intended to limit the scope of the present invention.

[0089] [Manufacturing of sealing film] Example 1 LUCENE, an ethylene / 1-butene copolymer from LG Chem TM500 g of LF675 was dried overnight in a convection oven at 40°C. TM The density of LF675 measured according to ASTM D1505 is 0.877 g / cm 3 The melt index (190°C, 2.16 kg) measured according to ASTM D1238 was 14.0 g / 10 min. The bowl temperature of the viscometer (Haake Modular Torque Viscometer, Thermo Electron (Karsruhe) GmbH) was set to 40°C. After the ethylene / 1-butene copolymer was added to the bowl, 1 phr (parts per hundred rubber) of t-butyl 1-(2-ethylhexyl) mono-peroxycarbonate (TBEC, Sigma-Aldrich) was added as a crosslinking agent, 0.375 phr of triallyl isocyanurate (TAIC, Sigma-Aldrich) and 0.125 phr of tetravinyltin (TVT, Sigma-Aldrich) were added as a crosslinking coagent using an electric pipette, and 0.2 phr of methacryloxypropyltrimethoxysilane (MEMO, Shin-Etsu) was added as a silane coupling agent. The change in torque value over time was observed while stirring at 40 rpm, and the impregnation was terminated when the torque value increased sharply.

[0090] Next, the impregnated sample was press-molded using a micro extruder at a low temperature (extruder barrel temperature 90 to 100°C) so that high-temperature crosslinking would not occur, to an average thickness of 0.5 mm, to produce a sheet-shaped encapsulant film.

[0091] Examples 2 to 5 An encapsulant composition for optical elements and an encapsulant film were produced in the same manner as in Example 1, except that the amounts of triallyl isocyanurate (TAIC) and tetravinyltin (TVT) used as crosslinking assistants were varied as shown in Table 2 below.

[0092] Comparative Example 1 Example 1: LUCENE TMAn encapsulant composition for optical elements and an encapsulant film were produced in the same manner as in Example 1, except that ethylene vinyl acetate (EVA, EP28025, manufactured by LG Chemical Co., Ltd.) was used instead of LF675, and 0.5 phr of triallyl isocyanurate (TAIC) was used as the crosslinking assistant.

[0093] Comparative Example 2 An encapsulant composition for optical elements and an encapsulant film were produced in the same manner as in Example 1, except that no crosslinking auxiliary was used.

[0094] Comparative Example 3 An encapsulant composition for optical elements and an encapsulant film were produced in the same manner as in Example 1, except that only triallyl isocyanurate (TAIC) was used in an amount of 0.5 phr as the crosslinking assistant.

[0095] Comparative Example 4 An encapsulant composition for optical elements and an encapsulant film were produced in the same manner as in Example 1, except that 0.5 phr of triallyl isocyanurate (TAIC) and 0.5 phr of tetravinylsilane (TVS) were used as crosslinking assistants.

[0096] Comparative Example 5 An encapsulant composition for optical elements and an encapsulant film were produced in the same manner as in Example 1, except that 0.5 phr of tetravinylsilane (TVS) alone was used as the crosslinking assistant.

[0097] Comparative Example 6 An encapsulant composition for optical elements and an encapsulant film were produced in the same manner as in Example 1, except that 0.25 phr of triallyl isocyanurate (TAIC) and 0.25 phr of tetravinylsilane (TVS) were used as crosslinking assistants.

[0098] [Table 1]

[0099] In Table 1, POE represents ethylene-1-butene copolymer, EVA represents ethylene vinyl alcohol, TAIC represents triallyl isocyanurate, TVT represents tetravinyltin, and TVS represents tetravinylsilane.

[0100] Experimental Example [Analysis of encapsulant film] The 0.5 mm thick encapsulant film (15 cm x 15 cm) prepared above was placed between two release films (thickness: about 100 μm), and crosslinked by lamination using a vacuum laminator at a process temperature of 150° C. for a process time of 20 minutes (5 minutes vacuum / 1 minute pressure / 14 minutes pressure maintenance).

[0101] (1) Impregnation speed In the above Examples 1 to 5 and Comparative Examples 1 to 6, the prepared encapsulant compositions for optical elements were stirred at 40° C. and 40 rpm, and the time to complete impregnation of the crosslinking agent was measured and shown in Table 3. The impregnation torque value was measured according to the stirring time during impregnation, and impregnation torque curves were created as shown in FIGS.

[0102] (2) Volume resistivity Measurements were performed at a temperature of 23±1°C and a humidity of 50±3% using an Agilent 4339B High-Resistance meter (Agilent Technologies) while applying a voltage of 1000 V for 600 seconds.

[0103] (3) Light transmittance Using a Shimadzu UV-3600 spectrophotometer, the light transmittance was measured from 200 nm to 1,000 nm to obtain a light transmittance curve, and then the values ​​from 280 nm to 380 nm and 380 nm to 1,100 nm were confirmed.

[0104] -Measurement mode: Transmittance -Wavelength interval: 1nm - Measurement speed: medium

[0105] (4) Adhesion measurement 40% of the glass substrate area was covered with an encapsulant film, and the remaining 60% was covered with a polyimide film, and then a fluorine-based solar backsheet was laminated on top of that. The lamination was performed at a temperature of 150°C for 20 minutes so that the encapsulant film was crosslinked and attached to the glass substrate. The encapsulant film of the test piece was cut to a width of 1 cm so that the width of the measurement area was 1 cm.

[0106] A UTM sample holder and a 1 kN load cell were attached to a tensile compression tester (LRX Plus Universal Test Machine, manufactured by LLOYD), and the encapsulant film attached to the glass substrate and the end of the part of the glass substrate where the encapsulant film was not attached were fixed, respectively, and then the adhesion was tested by pulling at 60 mm / min.

[0107] (5) Crosslinking degree measurement The crosslinked sheet was cut into 3 × 3 mm pieces using scissors. 2 Cut to size: 7×10cm 2 The sides and bottom of a 200 mesh iron net were sealed with staples. The sheet was placed in the iron net and the weight of the sheet was measured. The amount of the sheet was adjusted to 0.49 to 0.51 g. After the sheet was placed, the top of the iron net was sealed with staples and the total weight of the sample was measured. A solution of 10 g of BHT (dibutylhydroxytoluene) in 1,000 g of xylene was poured into a 2 L cylindrical reactor and 3 to 4 of the above samples were placed in it. The reflux was stopped 5 hours after the reactor was heated and started to boil. The sample in the reactor was taken out with a metal net and washed with xylene. It was vacuum dried overnight at 100°C. The weight of the dried sample was measured and the degree of crosslinking was calculated. The degree of crosslinking can be determined as the average value of 3 to 4 samples refluxed with xylene.

[0108] Crosslinking degree (%) = [(weight of sheet before reflux) / (weight of sheet after reflux)] × 100

[0109] [Table 2]

[0110] Referring to Table 2, it can be seen that the optical element encapsulant compositions of Examples 1 to 5 exhibit higher volume resistance after crosslinking than the optical element encapsulant compositions of Comparative Examples 1 to 6. Such results were not only observed in Comparative Example 1, which uses EVA, which is commonly used instead of an olefin-based copolymer, as the resin component, but also in Comparative Examples 2 to 6, which use an ethylene-1-butene copolymer as in the Examples. This confirmed that the tetravinyltin (TVT) used in Examples 1 to 5 caused the optical element encapsulant compositions to exhibit higher volume resistance after crosslinking. In addition, it was confirmed that Examples 1 to 5 showed an improved crosslinker impregnation speed compared to Comparative Example 3, which uses 0.5 phr of triallylisocyanurate (TAIC), and that the crosslinker impregnation speed increases as the usage ratio of tetravinyltin (TVT) increases. Examples 1 to 3 are examples in which both tetravinyltin (TVT) and triallylisocyanurate (TAIC) were used, and Examples 4 and 5 are examples in which tetravinyltin (TVT) was used alone. It was confirmed that it is possible to use tetravinyltin (TVT) alone or a mixture of tetravinyltin (TVT) and triallylisocyanurate (TAIC), and that the mixing ratio can be determined by increasing the amount of tetravinyltin (TVT) used to increase the volume resistivity after crosslinking, and by increasing the amount of triallylisocyanurate (TAIC) used to increase the degree of crosslinking. In addition, when tetravinyltin (TVT) is used alone, it is possible to obtain a more improved volume resistivity value after crosslinking, and it was confirmed that even when tetravinyltin is used alone, a high level of crosslinking degree improvement effect can be obtained.

Claims

1. (1) an olefin copolymer; (2) a crosslinking agent; and (3) a silane coupling agent; (4) An encapsulant composition for optical elements, comprising: 【Chemistry 1】 In the above Chemical Formula 1, l, m, n, and o are each independently an integer of 0 to 4.

2. The encapsulant composition for optical elements according to claim 1 , wherein the olefin-based copolymer (1) satisfies the following requirements: (a) a density of 0.85 to 0.90 g / cc; and (b) A melt index (190° C., 2.16 kg) measured in accordance with ASTM D1238 of 0.1 to 100 g / 10 min.

3. 2. The encapsulant composition for optical elements according to claim 1, wherein the olefin copolymer (1) is an ethylene alpha-olefin copolymer.

4. The (1) olefin copolymer has a volume resistivity of 1.0×10 15 2. The sealing material composition for optical elements according to claim 1, which is an ethylene alpha-olefin copolymer having a resistivity of Ω·cm or more.

5. 2. The encapsulant composition for optical elements according to claim 1, wherein the crosslinking agent is one or more selected from the group consisting of organic peroxides, hydroperoxides and azo compounds.

6. The crosslinking agent may be t-butylcumyl peroxide, di-t-butyl peroxide, di-cumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, t-butyl hydroperoxide, bis-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, t-butylperoxyisobutyrate, or t-butylperoxyacetate. 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne, methyl ethyl ketone peroxide, cyclohexanone peroxide, azobisisobutyronitrile, and azobis(2,4-dimethylvaleronitrile).

7. The encapsulant composition for optical elements according to claim 1, wherein the silane coupling agent is at least one selected from the group consisting of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane (MEMO), vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and p-styryltrimethoxysilane.

8. 2. The encapsulant composition for optical elements according to claim 1, wherein in Chemical Formula 1, l, m, n, and o each independently represent an integer of 0 to 2.

9. The encapsulant composition for optical devices according to claim 1 , wherein the compound of Chemical Formula 1 is tetravinyltin.

10. The encapsulant composition for optical elements is (1) 80 to 99 parts by weight of an olefin copolymer, (2) 0.1 to 9 parts by weight of a crosslinking agent, (3) 0.01 to 2 parts by weight of a silane coupling agent, and (4) The encapsulant composition for optical elements according to claim 1, comprising 0.1 to 9 parts by weight of the compound of Chemical Formula 1.

11. The encapsulant composition for optical elements further includes (5) a crosslinking assistant other than the compound of Chemical Formula 1, The encapsulant composition for optical elements according to claim 1 , wherein the (5) crosslinking assistant agent includes a compound containing one or more allyl groups or (meth)acryloxy groups.

12. The encapsulant composition for optical elements according to claim 11, wherein the (5) crosslinking auxiliary comprises at least one selected from the group consisting of triallyl isocyanurate (TAIC), triallyl cyanurate, diallyl phthalate, diallyl fumarate, diallyl maleate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, and trimethylolpropane trimethacrylate.

13. The encapsulant composition for optical elements according to claim 10, wherein a weight ratio of the compound of formula 1 (4) and the crosslinking auxiliary (5) is 20:80 to 80:

20.

14. An encapsulant film for optical elements comprising an olefin copolymer and a compound represented by the following chemical formula 1: 【Chemistry 2】 In the above Chemical Formula 1, l, m, n, and o are each independently an integer of 0 to 4.

15. An optical element module comprising an optical element and the encapsulant film for optical elements according to claim 14 .

Citation Information

Patent Citations

  • Manufacturing method of puncture-resistant high-strength frozen polyethylene film

    CN112940376A

  • Sealing material for solar cell module and solar cell module

    JP2017195243A

  • Composition for sealing material film and sealing material film containing the same

    JP2022551096A

  • Crosslinking aid composition for olefin copolymers, crosslinking agent composition, and additive for sealing material composition for optical elements

    JP2024524855A

  • KR2018-0063669